Responsiveness of temperature using tunable dual-wavelength Q-switched fiber laser - Zamri, A Z M; Zalkepali, N U H H; Awang, N A; Mustafa, M K; Mahmud, N N H E N; Muhammad, N A M (IOP, 2023)
In this paper, a responsiveness temperature based on a tunable dual-wavelength Q-switched fiber laser has been proposed and experimentally demonstrated. Experiments have been carried out with tunable dual-wavelength Q-switched fiber laser by using graphite as a saturable absorber, which is incorporated in the two fiber Bragg gratings (FBG) as a sensing element. Both FBG 1 and FBG 2 have a central wavelength of 1550 nm and 1551 nm, respectively. The optical spectral and RF signals are proven observed during the temperature change. The results from optical spectra demonstrate the measured temperature has good linearity, where the slope of the graph is thus the temperature sensitivity of 1550 nm FBG. The R2 value of the graph is 0.965 and the value of temperature sensitivity is 0.0064 nm ◦C −1 . For FBG 2 as the sensing element, the R2 value of the graph is 0.9751 and the value of temperature sensitivity is 0.0068 nm ◦C −1 . In addition, the repetition rate is almost linear with the temperature change, giving the correlation factor of R2 value of FBG 1 and FBG 2 are 0.8118 and 0.9046, respectively. The experimental results prove the feasibility of the proposed temperature sensor.